1997
DOI: 10.1074/jbc.272.11.7223
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and Inhibitor Specificity of Interleukin-1β-converting Enzyme and Related Caspases

Abstract: Interleukin-1␤-converting enzyme (ICE) is a novel cysteine protease responsible for the cleavage of pre-interleukin-1␤ (pre-IL-1␤) to the mature cytokine and a member of a family of related proteases (the caspases) that includes the Caenorhabditis elegans cell death gene product, CED-3. In addition to their sequence homology, these cysteine proteases display an unusual substrate specificity for peptidyl sequences with a P 1 aspartate residue. We have examined the kinetics of processing pre-IL-1␤ to the mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(168 citation statements)
references
References 37 publications
9
158
1
Order By: Relevance
“…Interestingly, we found that the level of cleaved PARP was also similar in the HeLa cells infected with either DA or GDVII wt viruses (Fig. 5B), perhaps because a number of caspases can cleave PARP, including caspase-9 (15).…”
Section: Da L Is Proapoptotic In Hela Cells Following Da Virus Infectmentioning
confidence: 77%
“…Interestingly, we found that the level of cleaved PARP was also similar in the HeLa cells infected with either DA or GDVII wt viruses (Fig. 5B), perhaps because a number of caspases can cleave PARP, including caspase-9 (15).…”
Section: Da L Is Proapoptotic In Hela Cells Following Da Virus Infectmentioning
confidence: 77%
“…After 5-h cell serum starvation, apoptosis in sst2-expressing cells was 3.6-71.2-fold higher than in mock cells (5.670.8 versus 1.570.5% of apoptotic cells, respectively) ( Figure 1a). Cell treatment with the specific executioner caspase competitive inhibitor DEVD-CHO (uncleavable substrate) 13 abrogated sst2-mediated apoptosis, and reverted apoptosis levels in NIH3T3/sst2 to those observed in mock cells (NIH3T3/mock) ( Figure 1a). By using a cell viability assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT)), we showed as well that sst2 decreased cell viability in NIH3T3/ sst2 to 7271.3% of mock cells (Figure 1b).…”
Section: Resultsmentioning
confidence: 98%
“…The kinetic of NO generation from NCX-4016, however, is different from that of SNAP. In fact, the NO moiety of NCX-4016 dissociates slowly from aspirin, resulting in a lower, but sustained, release of NO; third, further supporting the view that the inhibitory activity of NCX-4016 on cytokine release was due to its NO moiety, we demonstrated that substituting the nitrooxymethyl-phenyl ester group, the NO moiety, with an hydroxymethyl-phenyl group resulted in a compound, the NCX-4017, highly cytotoxic, devoid of any pharmacological activity; fourth, NCX-4016 activates NOdependent pathways as demonstrated by the finding that incubating the cells with ODQ, to prevent guanosilyl cyclase activation, almost completely inhibited changes in [cGMP] i , although it had no effect on cytokines release (17); fifth, incubating monocytes with LPS resulted in a time-dependent activation of ICE-like endoproteases, an effect that was almost completely prevented by cotreating cells with NCX-4016, but not with aspirin or NCX-4017; sixth, inhibition of LPS-induced YVAD cleaving activities by NCX-4016 was reverted by DTT, an agent that effectively removes thiolbound NO groups from proteins (17,19,20,27,32); seventh, exposure to HgCl 2 , an agent that bind to thiol group, displaced NO from lysates obtained from NCX-4016-treated monocytes and resulted in a DTT-reversible inhibition of YVADase activity, indicating that the NO removed by HgCl 2 was bound to a cysteine group (17,19,20,27,32); and, finally, incubating LPS-challenged monocytes with NCX-4016, but not with aspirin, prevented ICE activation as measured by assessing the release of the p20 subunit (23,33). Taken together, these data demonstrated that incubating human monocytes with NCX-4016 results in intracellular NO formation and S-nitrosation/inhibition of ICE-like cysteine proteases involved in pro-IL-1␤ and pro-IL-18 processing (10 -12).…”
Section: Discussionmentioning
confidence: 98%